2022
DOI: 10.11591/ijeecs.v27.i1.pp366-374
|View full text |Cite
|
Sign up to set email alerts
|

The design of viscometer with smartphone controlling

Abstract: New design of a viscometer based on the s tokes viscosity measurement method is proposed. The principle of operation of this viscosimetr is based on the use of ball periodic alternated movement in a horizontally positioned cuvette that filled with the test liquid. The movement appears under the in fluence of a magnetic field that created by two electromagnets. Registration of the ball movement inside the cuvette is carried out using an optoelectronic pair. A distinctive feature of the proposed design is contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Moreover, it is possible to significantly simplify its solution by using equipment interfaced with the user’s smartphone via a radio channel. This φ [ 157 , 158 , 159 ] has several other purposes, including the creation of new equipment for viscometric measurements. In the cited works, it was shown that the computing capabilities of modern smartphones make it possible to significantly simplify the electronic circuits of measuring equipment, i.e., the task of creating methods for direct radio engineering differentiation of the dependence of the optical density of a solution on temperature is indeed solvable.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is possible to significantly simplify its solution by using equipment interfaced with the user’s smartphone via a radio channel. This φ [ 157 , 158 , 159 ] has several other purposes, including the creation of new equipment for viscometric measurements. In the cited works, it was shown that the computing capabilities of modern smartphones make it possible to significantly simplify the electronic circuits of measuring equipment, i.e., the task of creating methods for direct radio engineering differentiation of the dependence of the optical density of a solution on temperature is indeed solvable.…”
Section: Resultsmentioning
confidence: 99%
“…Suleimenov IE [3] et al studied a system to control the automatic verification of a viscometer with a smartphone. Saxena Indu [4] et al used a platinum wire level sensor to detect the liquid level.…”
Section: Introductionmentioning
confidence: 99%